CD30 Expression in Germinal Center B-cell-like and non-Germinal Center B-cell-like Subtypes of Diffuse Large B-cell Lymphoma - Julianty, Patricia Fransisca; Ham, Maria Francisca; Kusmardi, Kusmardi; Harahap, Agnes Stephanie (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Diffuse large B-cell lymphoma (DLBCL) is the most common and most heterogeneous type of non-Hodgkin lymphoma. With current therapeutic modalities, 30%–40% of DLBCL cases still experience recurrence. The discovery of CD30 expression in DLBCL in several studies has opened up alternative opportunities for new target therapies. AIM: This cross-sectional study aimed to determine CD30 expression in DLBCL and its difference in expression in germinal center B-cell such as (GCB) and non-GCB subtypes. METHODS: The sample consisted of 25 GCB and 25 non-GCB cases based on immunohistochemical examination performed at Cipto Mangunkusumo Hospital from 2014 to 2017. CD30 staining was carried out and assessed using tumor cells percentage with positive cutoff values of >0%, >10%, and >20%. RESULTS: Positive CD30 expression was obtained in 8 (16%), 4 (8%), and 3 (6%), out of 50 DLBCL cases with positive cutoff values of >0%, >10%, and >20%, respectively. We performed Fisher’s exact test to determine CD30 expression in the GCB and non-GCB subtypes and found no significant difference with p > 0.05. CONCLUSION: Our study found no significant difference between CD30 expression in the GCB and non-GCB subtypes of DLBCL.